Prospects for use of condensed gases and supercritical fluids in phytochemical production - Demyanenko, D; Breusova, S; Karpenko, L (Annals of Mechnikov’s Institute, 2019)
In the given review article analysis of the literature and patent sources concerning main methods for intensification of extraction processes of medicinalvegetative raw materials – use of condensed gases and supercritical fluids (SCF) on more acceptable extractants has been carried out for last20 years. Urgency of the specified technologies consists in need for replacement of traditional extraction methods on power- and time-saving ones, and also in use of nontoxic, fire-proof and low-boiling solvents because the most of routine organic solvents (ethanol, methanol, acetone, chloroform, ethylacetate, etc.) are toxic and/or flammable or expansive and rather hard to evaporate out from extracts obtained. The abovementioned trends are the most universal for intensification of extraction processes and sometimes purification of final or intermediate products acceptable for commercial scale of manufacture. The main advantages and disadvantages of the givenmethodsare compared for different plant species and groups of biologically active substances (BAS). It has been shown that in most cases supercritical СО2(SC-СО2)are inferiorin its dissolving ability to number of condensed gases and, besides, such technology is much more expensive. The range of BAS taken with SC-СО2 is limited to mainly lipophilic compounds because of zero electrical dipole moment of SC-СО2 and its low polarity. As extractants alternative to SC-СО2 with higher dissolving ability SC - ethane, nitrogen monoxide, freons - R134а, R23, R32, R408 and number of others can be used. Also to enlarge range of extractable BAS it is possible to add different cosolvents, mainly ethanol or methanol in quantity up to 20%. At the same time in phytochemical production prospective alternatives to liquid or supercritical СО2 are certain condensed gases with wider range of physico-chemical properties: fluorinated derivatives of hydrocarbons (freons), liquid ammonia, dimethyl ether (DME), sulfur hexafluoride (insulating gas) or their mixtures, etc. Their major characteristics include lower vapor pressure if compared with liquid СО2, antimicrobic activity allowing to solve one the main problem in phytochemical production – microbial contamination of extracts (and other herbal drug preparations), possibility to extract not only lipophilic, but also more polar substances depending on choice of solvents or their mixes and their higher extraction rate.It has been found that some kinds of freons (for example, R22) due to their higher polarity are able to take wider spectrum of BAS than liquid СО2: essential and fat oils, fat-soluble vitamins, coumarins, carotenoids, phenolic alcohols, valrates, iridoids, some alkaloids and flavonoids. Besides, certain freons (for example, С318) have very high selectivity allowing to extract essential oils without accompanying fats. Some condensed gases, such as liquid ammonia, dimethyl ether and difluoromethane (freon R32) can be used as well for obtaining of hydrophilic BAS (saponins, alkaloids, flavonoids). Thus such solvents should be polar enough or can be mixed with polar modifiers. Supercriticalfluids and some subcritical condensed gases are suitable for fractionatingof primary (crude) extracts because their selectivity considerably depends on temperature, pressureand composition (in case of mixtures with each other or with cosolvents). Also high selectivity of condensed gas and SCFs is shown in near-critical areas. Very important property of most of condensed gases and SCFs is their ability to considerably reduce microbial contamination of extracts in comparison with initial plant raw materials. Conclusions. Among existing methods for intensification of stage of plant extraction the most applicable for commercial scale is use of condensed gases and supercritical fluids as extractants. It is found that for today in the world the most widespread SCF is carbon dioxide. The main lacks of СО2 as an extractant are high working pressure and narrow spectrum of extractable BAS which is limited only to lipophilic substances. This induces the search for alternative condensed gases and SCF among which fluorohydrocarbons (freons) are of the greatest interest. Also perspective methods of extraction intensification are applications of ultrasound, microwave field and some other methods of raw material processing, but meanwhile they have not got industrial value because of insufficient scientific base.